2017
DOI: 10.1177/2041669517717500
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Lip Color on Perceived Lightness of Human Facial Skin

Abstract: Whereas geometric illusions in human faces have been reported by several studies, illusions of color or lightness in faces have seldom been explored. Here, we psychophysically investigated whether lip color influences facial skin's perceived lightness. Results of Experiment 1 demonstrated that redder lips lightened and darker lips darkened the perceived complexion. These lightness or darkness inducing effects differ from the classical illusion of lightness contrast in nonface objects for two reasons. First, il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Because skin evenness affects judgments of age, health, and beauty (Fink et al, 2006;Fink et al, 2001), we propose that makeup makes faces appear younger (Russell et al, 2019), healthier (Nash, Fieldman, Hussey, Leveque, & Pineau, 2006), and more attractive (Batres et al, 2019a) in part through the contextual modulation of skin appearance that we have shown here. It has been shown that lip color can affect the perceived lightness and hue of facial skin (Kiritani, Okazaki, Motoyoshi, Tanako, & Ookubo, 2017;Kobayashi et al, 2017). Our findings join these in supporting the claim that makeup applied to the facial features affects skin appearance.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Because skin evenness affects judgments of age, health, and beauty (Fink et al, 2006;Fink et al, 2001), we propose that makeup makes faces appear younger (Russell et al, 2019), healthier (Nash, Fieldman, Hussey, Leveque, & Pineau, 2006), and more attractive (Batres et al, 2019a) in part through the contextual modulation of skin appearance that we have shown here. It has been shown that lip color can affect the perceived lightness and hue of facial skin (Kiritani, Okazaki, Motoyoshi, Tanako, & Ookubo, 2017;Kobayashi et al, 2017). Our findings join these in supporting the claim that makeup applied to the facial features affects skin appearance.…”
Section: Discussionsupporting
confidence: 85%
“…We attributed this effect to the fact that faces are processed holistically, involving less decomposition into parts and greater spatial integration than other objects (Farah, Wilson, Drain, & Tanaka, 1998), including for judgments of facial age (Hole & George, 2011). Similarly, a recent psychophysical study found that lip color affects perceived skin lightness, and the authors proposed that this is due to holistic processing (Kobayashi, Matsushita, & Morikawa, 2017). Yet there is another way that contrast around the facial features might affect the appearance of surrounding skin, based on observations that apparent contrast can be modulated by surrounding image content (Bex, Mareschal, & Dakin, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Although the area of vermilion makes up only a small fraction of the total facial area, the redness of the vermilion profoundly affects the impressions of others. A redder vermilion lightens the perceived complexion [1], and a red vermilion increases the facial attractiveness of female Caucasian faces [2,3]. The redness of the vermilion is thus an important factor affecting interpersonal impressions and face-to-face communication.…”
Section: Introductionmentioning
confidence: 99%
“…Lips can be associated to social relations as indicated in the p-value (.002) lesser than the alpha (0.05). Additionally, the lightness of facial skin becomes lighter when it was perceived made of lips that were more color red and the darker colored lips made it darker (Kobayashi, Matsushita, & Morikawa, 2017). Fuller lips had been considered more appealing compared to thin flat lips in traditional.…”
Section: Discussionmentioning
confidence: 99%